A surface site interaction point methodology for macromolecules and huge molecular databases. Issue 7 (15th March 2017) - Oliver, Antoni; Hunter, Christopher A.; Prohens, Rafel; Rosselló, Josep L.
Abstract : Determining the position and magnitude of Surface Site Interaction Points (SSIP) is a useful technique for understanding intermolecular interactions. SSIPs have been used for the prediction of solvation properties and for virtual co‐crystal screening. To determine the SSIPs for a molecule, the Molecular Electrostatic Potential Surface (MEPS) is first calculated using ab initio methods such as Density Functional Theory. This leads to a high cost in terms of computation time and is not compatible with the analysis of huge molecular databases. Herein, we present a method for the fast estimation of SSIPs, which is based on the MEPS calculated from MMFF94 atomic partial charges. The results show that this method can be used to calculate SSIPs for large molecular databases with a much higher speed than the original ab initio methodology. © 2017 Wiley Periodicals, Inc. Abstract : This study presents a very fast (10 3 faster than DFT) method for calculation of molecular electrostatic potential surfaces (MEPS) using partial atomic charges (MMFF94). The results suggest that the method is valid for predicting molecular H‐bond parameters (RMSD∼0.735), obtaining Surface Site Interaction Points (SSIP) for macromolecules and studying huge molecular databases.